Protective effects of betaine on the early fatty liver in laying hens through ameliorating lipid metabolism and oxidative stress - Chaohui Wang; Xi Sun; Xiaoying Liu; Yumeng Wang; Jiarui Luo; Xiaojun Yang; Yanli Liu (Frontiers in Nutrition)
IntroductionFatty liver syndrome (FLS) is a prevalent nutritional and metabolic disease that mainly occurs in caged laying hens, causing substantial losses in the poultry industry. The study was carried out to explore the protective effect and potential mechanism of betaine on early FLS.MethodsThere were three groups: Con group (basal diet), FLS group (Dexamethasone injection + basal diet) and betaine group (Dexamethasone injection + basal diet with 8 g/kg betaine). Birds in FLS and betaine groups were treated with subcutaneous dexamethasone injection once a day at a dosage of 4.50 mg/kg body weight for 7 days.ResultsThe results revealed that DXM treatment significantly increased the liver index, serum aspartate aminotransferase (AST), total protein (TP), total bilirubin (TBIL), total biliary acid (TBA), total cholesterol (TC), high density lipoprotein cholesterol (HDL-c), low density lipoprotein cholesterol (LDL-c), and glucose (GLU) (p < 0.05). Additionally, hepatic TC and TG levels were also elevated (p < 0.05). Meanwhile, H&E and oil red O staining showed that there were a large number of vacuoles and lipid droplets in the liver of hens in FLS group. Dietary betaine addition significantly alleviated the increasing of serum TBIL, TBA and hepatic TC caused by dexamethasone treatment (p < 0.05). There existed 1,083 up- and 996 down-regulated genes in FLS group when compared with the control, and there were 169 upregulation and 405 downregulation genes in BT group when compared with FLS group. A total of 37 differential expression genes (DEGs) were rescued by betaine addition, which were related to lipid metabolism and antioxidant functions including APOC3, APOA4, G0S2, ERG28, PLA2G3, GPX4 and SLC5A8. Serum metabolomics analysis showed that 151 differential metabolites were identified in FLS group when compared with the control. Dietary betaine addition could rescue the changes of metabolites partly such as chicoric acid, gamma-aminobutyric acid, linoleic acid, telmisartan, which were associated with anti-oxidative function. In addition, RT-PCR results showed that genes involved in lipid metabolism, such as ACC, FAS, SCD1, ELOVL6, SREBP1, GR, ATGL and MTTP were markedly upregulated at the mRNA level (p < 0.05). However, dietary supplementation with betaine can reversed the expression of these genes (p < 0.05). Importantly, dietary betaine supplementation could reverse increased lipid synthesis partly by regulating PI3K/AKT/SREBP and CEBPα pathways in the liver based on western blot results (p < 0.05).ConclusionDexamethasone treatment could establish the early FLS model in laying hens with hepatic lipid accumulation and no inflammation, which could be attenuated by dietary betaine addition.